Integration of experimental activities into remote teaching using a quadrotor test-bed. Issue 12 (2021) - Invernizzi, Davide; Panza, Simone; Giurato, Mattia; Yang, Guitao; Chen, Kaiwen; Lovera, Marco; Parisini, Thomas
Abstract: The role of laboratory activities in engineering education is fundamental to enhance the students engagement and learning. In this paper we discuss the use of a laboratory test-bed for education and research developed to replicate the dynamic behavior and the control design challenges of an underactuated multirotor Unmanned Aerial Vehicle (UAV), which is becoming a game-changing technology in several application fields. In view of recent challenges related to online teaching activities, the setup has been endowed with a remotization kit to allow students to access the system from anywhere with an internet connection and to perform experiments with satisfactory results. The experience gathered in integrating laboratory activities with the proposed test-bed into the undergraduate Control Systems module at Imperial College London is reported. The paper presents the development and organization of the remote laboratory lectures and provides an overview of the obtained results.